Efek Penambahan Limbah Sayuran Dalam Pembuatan Vermikompos Feses Sapi Dengan Menggunakan Cacing Anc (Eudrilus Eugeniae) Terhadap Kualitas Kimia - Setiawan, Dimas; Syarifuddin, Hutwan; Novianti, Sri (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aims to determine the effect of adding vegetable waste on the chemical quality of cow feces vermicompost using ANC earthworms. The study was conducted at the Animal and Forage Cultivation Laboratory, Faculty of Animal Husbandry, University of Jambi for one month using a Completely Randomized Design (CRD) with four treatments and five replications. The treatment consisted of adding vegetable waste as much as V1 (200 g), V2 (250 g), V3 (300 g), and V4 (350 g) mixed with 300 g of cow feces and 25 g of ANC earthworms. The parameters observed included the content of Carbon (C), Nitrogen (N), Phosphorus (P), Potassium (K), C/N ratio, and pH. The results showed that the addition of vegetable waste had a very significant effect (P<0.01) on C, N, and P levels, a significant effect (P<0.05) on K, but no significant effect (P>0.05) on vermicompost pH. The best treatment was V2, with a C content of 5.07%, N 0.28%, P 3.08%, K 0.74%, and a C/N ratio of 12.19. The combination of vegetable waste and cow manure in a balanced ratio produced vermicompost with chemical qualities that met organic fertilizer standards. The addition of vegetable waste also increased the activity of worms and microorganisms, accelerated decomposition, and increased nutrients that are beneficial for soil fertility and plant growth.